Self-Compassion and Psychological Well-Being Among Malaysian Counselors: The Mediating Role of Resilience - Voon, Siok Ping (Springer Science and Business Media LLC, 2021)
This study investigated the associations between self-compassion, resilience, and psychological well-being among 408 counselors in Malaysia. Data were collected by using a web-based survey. PLS-SEM analyses revealed that self-compassion was positively related to counselors’ resilience and psychological well-being, whereas resilience was positively related to counselors’ psychological well-being. Results also showed that resilience significantly mediated the associations between self-compassion and psychological well-being among counselors. The hypothesized model explained the substantial influences of self-compassion and resilience on counselors’ psychological well-being. This study highlighted the two important human factors, i.e., self-compassion and resilience, with implications for integrating these two influential constructs in the development of counselors’ psychological well-being.